Pendampingan Penerapan Kebijakan Penetapan Protokol Covid-19 Untuk Mendukung Pariwisata di Kota Semarang - Pranoto Pranoto; Tutik Tutik; Mukhammad Kholil Aswan (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
The policy issued by the Government an effort to overcome the increasingly severe spread of Covid 19 has caused various tourism industries to have a very significant impact. It is a concern to be discussed. With the policies implemented, it is scourge for the live and death of the tourism industry, starting from restrictions and closures to the termination of employees in the tourism industry. The purpose of this community service is to conduct an assessment and use the results as an academic formulation that can be proposed and implemented by the Government and industry players in reviving Semarang City tourism so that it will provide support for economic turnover and regional income. This community service uses a descriptive method by reviewing the policies applied to the tourism industry. The result obtained in this service are the motivation to stay afloat for tourism actors realized by product packaging and promotions adapted to the current situation in the domestic and international scope. However, the obstacle is the existence of policies that often change, so that tourism industry players must continuously adjust the regulations set by the Government. The conclusion drawn is the decree of rules carried out repeatedly with close and overlapping time intervals eventually lead to inhibition/ termination of the tourism insdustry business in Semarang.